Managing the Implementation of the Merdeka Curriculum Education for Sustainable Development through an Evaluation Study in Educational Practice - Yunita Wijayanti; Md Tariqul Islam (International Journal of Advanced Studies in Educational Management (IJASEM), 2026)
The integration of Education for Sustainable Development (ESD) within vocational education remains inconsistently implemented, particularly under Indonesia’s Merdeka Curriculum. This study evaluates how ESD principles are incorporated into the Accounting and Financial Institution program at SMK Muhammadiyah 1 Prambanan Klaten. A descriptive qualitative design was applied using the CIPP model. Data were collected through interviews, classroom observations, and document analysis involving school leaders, teachers, and students, and analyzed using interactive techniques with triangulation. The findings show that institutional vision and industry collaboration support ESD integration, and teachers have received relevant training; however, infrastructure limitations persist. Learning practices adopt student-centered and project-based approaches, yet implementation varies and supervision is limited. Although students meet technical competency standards, sustainability awareness and long-term career alignment remain weak. The study highlights the need to strengthen coherence between curriculum policy, pedagogical practice, and sustainability-oriented learning outcomes in vocational education.